Renal Transplant Pathology Serie Kidney allograft interstitial fibrosis and tubular atrophy (IFTA) due to specific causes: : Chronic calcineurin inhibitor toxicity - Mubarak, Muhammed (Pakistan Journal of Kidney Diseases, 2022)
Not applicable